2013
DOI: 10.4236/ojopm.2013.31003
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effects of Low Doses UV Radiation on Microporous Polysulfone Membranes in Sterilization Process

Abstract: Synthetic membranes have gained an important place in chemical technology and are used in a broad range of applications. UV irradiation is an age old process used for disinfection as well as for sterilization purposes. It is used for sterilizing equipment in which polysulfone (PSf) membranes are used. As a result, short time UV irradiation of polymer membranes has acquired importance in recent times. In the present study, microporous polysulfone membranes with 0.108 mm thickness have been prepared using phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…24 It has strong antimicrobial activity, but its ability to penetrate in solid matter is very poor and affects polymer molecular weight, chain length, polydispersity, branching, and chain termination. 25,26 Considering that each sterilization method has its advantages and limitations, the choice of a suitable process should be carefully studied according to the device features and final application. Further, the development of new processing technologies and the ability to control polymer structure and morphology at micro and nanoscale dimension arises new problems, especially if fiber alignment is one of the main features of the polymer membranes.…”
Section: Introductionmentioning
confidence: 99%
“…24 It has strong antimicrobial activity, but its ability to penetrate in solid matter is very poor and affects polymer molecular weight, chain length, polydispersity, branching, and chain termination. 25,26 Considering that each sterilization method has its advantages and limitations, the choice of a suitable process should be carefully studied according to the device features and final application. Further, the development of new processing technologies and the ability to control polymer structure and morphology at micro and nanoscale dimension arises new problems, especially if fiber alignment is one of the main features of the polymer membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristic peak around 3,200 to 3,550 cm −1 is assigned to hydroxyl stretching vibration, and the main ones in the range of 2,950–2,850 cm −1 are attributed to –C‐H stretching vibration. The wavenumbers around 1,350–1,550 cm −1 are associated with –SO 4 −2 and those observed in the range of 1,100 to 1,200 cm −1 are related to –C‐O stretching (Dehghani Kiadehi, Rahimpour, Jahanshahi, & Ghoreyshi, 2015; Rupiasih, Suyanto, Sumadiyasa, & Wendri, 2013). In the FT‐IR spectrum of PSF/TR‐100 membrane, the characteristic peaks at 600–3500 cm −1 remain unchanged with the incorporation of surfactant, demonstrating that the structure of PSF was well preserved.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have confirmed that the microstructure and the performance of PSF are affected by ultraviolet irradiation within a very short time of exposure, leading to simultaneous chain scission and crosslinking [16]. PSF photooxidation in an oxygen atmosphere leads to an oxidized surface with an increase in the relative amount of sulphur on the surface.…”
Section: Introductionmentioning
confidence: 90%